Delivering Social, Empathetic and Sustainable Architecture in Malaysia - Kuee, Shyuan (MAJ - Malaysia Architectural Journal, 2025)
Architecture plays a crucial role in shaping societies and environments, with a growing focus on its relation to equity and ecology amid global challenges like climate change and social inequality. Kuee Architecture’s work primarily focuses on creating inclusive communities that prioritise both people and the planet. The purpose of this paper is to study in depth, how each of their projects has considered some or all aspects of social, empathetic, and sustainable architecture. These projects will be explained in terms of their origins, design concepts and sustainability, before concluding on the positive impact each project has had on the community. Specific methods have been used for each project based on its relevance. More technical studies, such as daylight simulation studies, were applied to Galasa Event Place, where daylight was significant for the success of the project in terms of sustainability. Whereas for Pasar Pasir Pinji, detailed information on public engagement is provided to highlight the importance of stakeholder involvement in social architecture. Empathetic architecture was the main driver for the KLS Crematorium, as demonstrated by the careful and intricate design of the various spaces and the sequence of spaces for the mourning. 1 Lasam, a multiple award-winning project that was also included in the UIA 2030 Agenda, is the final project discussed. The success of all the applied aspects of social, empathetic, and sustainable architecture are demonstrated through the post-occupation surveys, its popularity among the community, and the efficiency of the building